PENGARUH KOMUNIKASI, KOMPETENSI DAN STRESS KERJA TERHADAP KINERJA KARYAWAN PADA PT. SURIATAMA MITRA PERWITA MEDAN - Andre Fitriano; Syintia Beby; Jesiska Tjokro; Wawan Logika (JURNAL MANAJEMEN, 2020)
The purpose of this study is to examine and analyze the influence of communication, competence and work stress on employee performance at PT. Suriatama Mitra Perwita Medan. The number of samples in this study were 108 respondents. The data analysis technique used multiple linear regression analysis. Communication has a positive and significant effect on employee performance at PT. Suriatama Mitra Perwita Medan. Competence has a positive and significant effect on employee performance at PT. Suriatama Mitra Perwita Medan. Job stress has a positive and significant effect on employee performance at PT. Suriatama Mitra Perwita Medan. Communication, competence and work stress have a positive and significant effect on employee performance at PT. Suriatama Mitra Perwita Medan. The coefficient of determination test results obtained an Adjusted R Square value of 0.249, this means 24.9% of the variables consisting of employee performance can explain the variation of the independent variables, namely free communication,competence and work stress while the rest is 75.1% (100% - 24.9%) explained by other variables not examined in this study, such as compensation, organizational climate, and, employee job placement.